E-Commerce Pemasaran Biji Dan Bubuk Kopi Berbasis Website Pada Mapaciko Roaster - Agus Romadhona, S. Kom; Bonitalia, S.Pd., M.Pd; Achsel Aldrian, S.Kom., MT; Monfari Kristofel Ajimu (Journal of Innovative and Creativity, 2025)
Coffee is a type of beverage that comes from the processing and extraction of coffee beans. There are three types of coffee that are famous in the world, namely Arabica Coffee, Robusta Coffee and Liberica Coffee. Mapaciko Roaster is one of the businesses engaged in the Coffee roaster sector. Mapaciko Roaster is located at Jalan Banteng, Palu City, Central Sulawesi. The problem that occurs is when selling or marketing coffee beans or powder at the Coffee roaster, where the sales or marketing system at Mapaciko Roaster still uses a traditional sales system and has a small scope. The purpose of this study is to produce an E-Commerce system that can help Mapaciko Roaster in developing all existing sales and purchase transactions. So that it can reach a wider market. This study uses the System Development Life Cycle (SDLC) Waterfall model method. This study uses 2 testing methods, namely blackbox testing and whitebox testing. From the results of testing carried out based on the blackbox testing method, all components of the save button and all login, add, edit, and delete buttons can function properly. Based on these results, this test is said to be successful with a value of 88.89% and this system can be categorized as "Very Good".